High susceptibility of magpie (Pica pica) to experimental infection with lineage 1 and 2 West Nile virus. - Nereida Jiménez de Oya; María-Cruz Camacho; Ana-Belén Blázquez; José-Francisc; Juan-Carlos Saiz; Ursula Höfle; Estela Escribano-Romero (Public Library of Science (PLoS), 2018)
West Nile virus (WNV), a zoonotic pathogen naturally transmitted by mosquitoes whose natural hosts are birds, has spread worldwide during the last few decades. Resident birds play an important role in flavivirus epidemiology, since they can serve as reservoirs and facilitate overwintering of the virus. Herein, we report the first experimental infection of magpie (Pica pica) with two strains of West Nile virus, lineages 1 (NY-99) and 2 (SRB Novi-Sad/12), which are currently circulating in Europe. Magpies were highly susceptible to WNV infection, with similar low survival rates (30% and 42.8%) for both lineages. All infected magpies developed viremia detectable at 3 days post-infection with titers above those necessary for successful transmission of WNV to a mosquito. Neutralizing antibodies were detected at all time points analyzed (from 7 to 17 days post-infection). WNV genome was detected in the brains and hearts of all magpies that succumbed to the infection, and, in some of the surviving birds. WNV-RNA was amplified from swabs (oral and cloacal) at 3, 6 and 7 days post-infection and feather pulps, from 3 to 17 days post-infection, of infected animals. Even more, infectious virus was recovered from swabs up to 7 days post-infection and from feather pulps up to 10 days post infection. Sham-infected control animals were negative for viremia, viral RNA, and antibodies. These results suggest that the magpie, which is one of the most abundant corvid species in Europe, could represent a source of WNV transmission for birds and humans. Our observations shed light on the pathogenesis, transmission, and ecology of WNV and can benefit the implementation of surveillance and control programs.